Studies on Preoperative Diagnosis for the Extension of the Carcinoma of the Papilla of Vater - Hashimoto, Naoki; Fukuda, Masaharu; Ashida, Hiroshi; Nishioka, Akihiko; Ishikawa, Yoshio; Utsunomiya, Joji; Kotoura, Yoshinao; Takahashi, Toku; Takagi, Kazumitsu (Nippon Shokaki Geka Gakkai zasshi, 1990)
To evaluate the preoperative diagnosis for the extension of the carcinoma of the papilla of Vater, we retrospectively compared 27 patients with this disease regarding the stage classification, prognostic factors, preoperative major symptoms, macroscopic appearance of the tumor, direct cholangiogrmas and hypotonic duodenograms.(1) Among the major symptoms, fever and abdominal pain were not distinctive between the stage. But the occurrence of jaundice and bilirubin level of 10 mg/dl appeared to be boundaries distinguishing stages I and II from stage III and IV.(2) Although many cases of protruding type were judged by macroscopic examination to be stage I or II, it seemed to be impossible to judge exactly the development of the disease by this method.(3) Neither direct cholangiograms of the distal bile duct nor hypotonic duodenograms was effective enough to make distinctive estimations. But in 22 of 27 cases (81%) simultaneous analysis of these two enabled us to estimate and classify distinctively between stages I and II and stages III and IV, and this was considered to be useful in selecting the operative method for the carcinoma of the papilla of Vater.